Synthesis, Molecular Characteristics, and Antibacterial Assessment of Marine Hydroid Aqueous Extract-Based Silver Bio-nanoparticles - Mandey, Fredryk; Arfan, Aulia Rhamdani; Arfah, Rugaiyah Andi (UI Scholars Hub, 2024)
This investigation aims to synthesize, analyze the molecularity, and test the ability of bacterial inhibition capability of silver nanoparticles that have been synthesized by simply mixing silver nitrate and aqueous extracts of marine natural products with and without the addition of amylum as a stabilizing agent. This research, with and without the addition of amylum as a stabilizing agent, obtained 39.0 and 55.2 mg of solids of round-shaped morphology silver nanoparticles with diameters of 87.9 and 103.0 nm., respectively. In addition, the antibacterial testing assay against Staphylococcus aureus and Escherichia coli showed some considerably good results. S. aureus with the addition of amylum had inhibition zone diameters of 8.55 and 7.45 mm, whereas without the addition of amylum had inhibition zone diameters of 7.82 and 7.22 mm. E. coli with the addition of amylum had inhibition zone diameters of 7.0 and 7.65 mm, whereas E. coli without the addition of amylum had inhibition zone diameters of 7.82 and 7.22 mm.